1997
DOI: 10.1093/oxfordjournals.jbchem.a021715
|View full text |Cite
|
Sign up to set email alerts
|

Acyltransferases and Transacylases Involved in Fatty Acid Remodeling of Phospholipids and Metabolism of Bioactive Lipids in Mammalian Cells

Abstract: Over 100 different phospholipid molecular species are known to be present in mammalian cells and tissues. Fatty acid remodeling systems for phospholipids including acyl-CoA: lysophospholipid acyltransferases, CoA-dependent and CoA-independent transacylation systems and lysophospholipase/transacylase are involved in the biosynthesis of these molecular species. Acyl-CoA:1-acyl-2-lysophospholipid acyltransferase prefers polyunsaturated fatty acyl-CoAs as acyl donors while acyl-CoA:2-acyl-1-lysophospholipid acyltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
230
1
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(237 citation statements)
references
References 138 publications
5
230
1
1
Order By: Relevance
“…The weak, but measurable lysoPE acyltransferase activity of mouse Aytl2, was detected in E. coli and reported in CHO-K1 microsomes (8). Enzymes with a similar specificity for lysoPC and lysoPE have also been reported in rat liver Golgi membranes (26) and other tissues (19).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The weak, but measurable lysoPE acyltransferase activity of mouse Aytl2, was detected in E. coli and reported in CHO-K1 microsomes (8). Enzymes with a similar specificity for lysoPC and lysoPE have also been reported in rat liver Golgi membranes (26) and other tissues (19).…”
Section: Discussionmentioning
confidence: 91%
“…Phospholipase-mediated deacylation, followed by reacylation of the lysophospholipid by using acyl-CoA, provides a pathway to remodel phospholipid molecular species in membranes. LPLAT activity, first described in the microsomal fraction of various tissues, has been characterized in many organisms (3,18,19).…”
Section: Discussionmentioning
confidence: 99%
“…It has traditionally been assumed that PL AA incorporation in activated cells may be secondary to the PLA 2 hydrolytic step because AA incorporates preferentially into the sn-2 position of PLs, and thus, for an enhanced AA reacylation to occur, 2-lysophospholipid acceptors, produced only by PLA 2 , should be provided. That lysophospholipid availability may limit AA reacylation in activated cells is also inferred from the finding that the specific activities of the enzymes of the reacylation pathway, ACSL and the CoA-dependent acyltransferases, are severalfold higher that that of PLA 2 in homogenates from resting and activated cells (23,(54)(55)(56)(57)(58).…”
Section: Discussionmentioning
confidence: 98%
“…Although various types of PLA 2 s have been identified and their biological functions were uncovered, the properties of LPLATs and their number have not been clarified. To date, numerous studies have suggested the possible presence of polyunsaturated long chain fatty acyl-CoA specific LPCATs, LPEATs, and LPSATs (5,(39)(40)(41)(42). Recently, we cloned and characterized two types of LPCAT: LPCAT1 and LysoPAFAT/LPCAT2.…”
Section: Discussionmentioning
confidence: 99%